Nine new Agrilus (Coleoptera: Buprestidae, Agrilini) from Palaearctic and Oriental regions - Jendek, Eduard; Nakládal, Oto (Zootaxa, 2019)
Nine new Agrilus from the Palaearctic and Oriental regions are described and illustrated: Agrilus baiocchii sp. nov. (India, Nepal, Pakistan, Thailand); A. baiyangling sp. nov. (China: Shaanxi); A. gorgan sp. nov. (Iran); A. graminis persicus ssp. nov. (Iran); A. iranopecirkai sp. nov. (Iran); A. muralis sp. nov. (China: Beijing); A. mus sp. nov. (Turkey); A. ressli sp. nov. (Iran); A. uzala sp. nov. (Russia: Primorye). The distributional range of A. araxenus Yablokov Khnzoryan, 1960 is updated.